DETERMINASI PERTUMBUHAN LABA BANK PEMBIAYAAN RAKYAT SYARIAH - Saida Marsa Nur Ahmadi (2023)
Increased profit growth is the achievement of BPRS success in its operational activities. This research aims to determine and analyze the effect of Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income (BOPO), Non-Performing Financing (NPF), Cash Ratio (CR), and the Sharia Supervisory Board (DPS) on profit growth. This research uses a quantitative method with secondary data in the form of annual financial reports from Sharia Rural Banks registered with the Financial Services Authority in the 2019-2021 period. The sampling technique used purposive sampling to obtain as many as 158 BPRS as samples. The data were processed and tested using panel data regression with the STATA-MP 13. This study obtained the results are (1) NPF has a negative effect on profit growth, where the lower the NPF will affect the profit growth obtained, (2) FDR has no effect on profit growth, this means that the high value of FDR has no effect on the profit growth generated, (3) BOPO has a negative effect on profit growth, so that a low BOPO value has an effect on profit growth earned, (4) CAR has a positive effect on profit growth, meaning that the higher the CAR value generated can affect the resulting profit growth, (5) CR has no effect on profit growth, which means that the high/low CR will not affect BPRS in increasing the resulting profit growth, (6) DPS has no effect on profit growth, meaning that the presence/absence of the DPS members has no effect on profit growth.